The Influence of Social Media Marketing and Attractiveness on Interest in Visiting the Kampong Melayu Tourism Village (BML) Pontianak City - Ariffin, Muchammad; Pratiwi, Windi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The research purposes are to analyze the influence of social media marketing and attractiveness on interest in visiting the Kampong Melayu Tourism Village (BML) Pontianak City. The tourist city of Kampong Melayu Pontianak relies heavily on social media marketing to attract tourists there. Therefore, in this instance, social media's accessibility and technological advancements indirectly served as a route for promotion to pique the attention of travelers. The attraction is crucial in generating interest in visiting the Pontianak settlement of Kampong Melayu. This feature has emerged as one of the most important elements in creating a favorable and alluring image for visitors, which can also benefit the tourism sector. The form of this research is quantitative, data is extracted and classified based on percentages. The sample in this research is people who visit the Kampong Melayu Tourism Village (BML) Pontianak City. Data analysis in this study used SmartPLS 3.0. The research results show that social media marketing has a positive effect on interest in visiting with a p-value of 0.000 < 0.05 and attractiveness also has a positive effect on interest in visiting with a p-value of 0.000 < 0.05. Social media marketing influences visiting interest by 28.9%, while attractiveness by 56.6%. The ability of social media to facilitate the widespread dissemination of information—as well as its appeal from a cultural perspective, plays a role in attracting tourist interest.